(untitled) (Journal of Information Technology and Digital World, 2023)
This research presents the development and implementation of an Electronic Health Record Management System (EHRMS) using Radio Frequency Identification (RFID) technology. The study discusses the limitations of traditional paper-based health record systems and highlights the benefits of integrating RFID technology in healthcare settings. The EHRMS streamlines patient identification and data capture processes, enhances data accuracy, and improves overall healthcare delivery. Real-time synchronization ensures up-to-date and easily accessible patient records, empowering healthcare providers to make informed decisions and provide timely interventions. The paper concludes with the potential impact of the RFID-based EHRMS in transforming healthcare record management and improving patient outcomes.